3PC-058 Robotic compounding: safety and productivity achievements in the preparation of hazardous drugs. (March 2019) - Lopez-Cabezas, C; Marín, AM; Riu, G; Codina, C; Soy, D
Abstract : Background: Robots arrived a few years ago to compounding units and, as a new health technology, it is necessary to assess their implications on safety and efficiency Purpose: Evaluate the impact on safety and productivity issues after the implementation of Kiro® Oncology. Material and methods: Failure mode, effect and criticality analysis were used to identify all risks related to the manual and robotic compounding processes. Criticality index (CI) was calculated for all of them, using a 1–4 scale. The percentage of preparations within the ±5% accuracy range was evaluated by gravimetric control for nine common drugs prepared manually and using the robotic system. To evaluate the role of the robot avoiding high-volume syringe handling, the number of preparations suitable to use 50 mL syringes (dose volume >20 mL) was estimated in a 6 month period (March–August 2018). Robot productivity (mean and maximum number of preparations) was evaluated during 6 months. Results: Twenty-three failure modes were identified in the manual system, ahead of 14 for the robotic process, with a global decrease in CI of 32%. Risks with the highest scores were related to labelling errors. Dosing accuracy was compared for 1031 manual preparations and 756 robotic preparations of carboplatin, cyclophosphamide, doxorubicin, epirrubicin, 5-fluorouracil, gemcitabine, irinotecan, oxaliplatin and paclitaxel. No statistically significant difference was observed between manual and robotic preparations (percentage within ±5%: 99.8% manual vs 96.9% robot; χ 2 =1.11, p=0.29). Doses above 20 mL prepared during the evaluation period were 730±56 (mean ±SD) per month. The mean number of daily preparations by the robot during the period studied was 50 (40% of total daily production), with a maximum of 90. Technical incidences and workflow interruptions were major obstacles in improving productivity. Conclusion: Robotic compounding might decrease the global risk of the process by the suppression of human intervention in some tasks. It showed similar accuracy rates to manual compounding in our setting. It has a major potential role avoiding stress injuries due to the repeated handling of high-volume syringes. Regarding productivity, the percentage of preparations assumed by the robot is still under expected; so, different strategies based on technical improvements and optimisation of cycle management should be implemented in the near future. References and/or acknowledgements: EJHP 2012;19:148. https://ejhp.bmj.com/content/19/2/148.2.info AJHP 2015;72(12):1036–45. No conflict of interest.